1981
DOI: 10.1111/j.2042-3306.1981.tb04129.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed monensin sodium toxicity in horses

Abstract: Summary Thirty‐two horses were examined with a history of poor performance and unthriftiness several months after the ingestion of feed containing monensin sodium. Cardiac abnormality was diagnosed in 8 cases and suspected in 4 others. Necropsy examinations were performed on 6 cases with marked clinical symptoms and evidence of circulatory failure was found. Marked cardiac myopathy and fibrosis was a consistent feature. It is concluded that ingestion of monensin sodium by horses may cause either acute death or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
1
1

Year Published

1983
1983
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 5 publications
5
32
1
1
Order By: Relevance
“…18,19 Typically, pathologic evidence of skeletal and cardiac myopathy along with a clinical history of possible or known exposure to monensin is used to confirm toxicosis. 8,13,16,17,20 However, several studies have shown individual variations in the severity of cardiac and skeletal muscle pathology, with some horses having no detectable histological changes 1,2,14 as shown in the current report. In those cases, diagnosis was made based on clinical signs of tachycardia, ataxia, depression, anorexia, and/or profuse sweating in conjunction with detection of high concentrations in the feed and/or stomach content.…”
Section: Research-article2014mentioning
confidence: 70%
See 1 more Smart Citation
“…18,19 Typically, pathologic evidence of skeletal and cardiac myopathy along with a clinical history of possible or known exposure to monensin is used to confirm toxicosis. 8,13,16,17,20 However, several studies have shown individual variations in the severity of cardiac and skeletal muscle pathology, with some horses having no detectable histological changes 1,2,14 as shown in the current report. In those cases, diagnosis was made based on clinical signs of tachycardia, ataxia, depression, anorexia, and/or profuse sweating in conjunction with detection of high concentrations in the feed and/or stomach content.…”
Section: Research-article2014mentioning
confidence: 70%
“…9 Several cases of monensin toxicosis in horses have been reported in the veterinary literature. 1,2,7,13,14 In all these cases, a diagnosis of monensin poisoning was based on finding high levels of monensin in the feed in association with appropriate clinical or histologic evidence of myopathy. To the authors' knowledge, a fatal monensin poisoning in horses has not been confirmed based on detection of monensin in tissues or blood.…”
mentioning
confidence: 99%
“…Fatal arrhythmias were previously reported as a cause of death in horses poisoned by monensin. 11,24 The 2 horses with cardiac disease (increased heart rates and cTnI values), but without physical signs of heart failure, had a gradual decline in heart rate and cTnI over time. In these horses, 17 (horse no.…”
Section: Discussionmentioning
confidence: 99%
“…Since they have good oral absorption (24,191), these products are quite toxic for mammalians and birds. Several accidents have been reported with overdoses of ionophores in mammalians, mostly involving acute intoxications, although reports of chronic intoxications have also appeared (156,162,170). Horses and rabbits seem to be particularly susceptible to ionophore intoxications (22).…”
Section: Vol 16 2003 Antimicrobial Growth Promoters In Animals 181mentioning
confidence: 99%